System approaches to school psychology (or why school psychologists shouldn't see kids). Issue 1 (June 2019) - Russell, Paul
Abstract: In a world where the only constant is change, schools are faced with the need to adapt creatively to changing societal demands, parental expectations, and children with increasingly diverse needs. Lasting and effective change can only occur with systemic and organisational change, and this essay argues that school-based psychologists are an invaluable, but potentially overlooked, resource in driving and supporting effective, evidence-supported, organisational change in schools. It is suggested that this can occur best when school-based psychologists are able to move away from direct service models that treat individual children to a systemic model that supports whole-school change.